The effect of fertilization with microfiltered liquid digestate on the quality parameters of Citrus fruits - Castellano, Angela; Selvaggi, Roberta; Mantovi, Paolo; Spina, Daniela; Hamam, Manal; Pappalardo, Gioacchino (Frontiers in Sustainable Food Systems, 2023)
Nowadays, the adoption of sustainable agricultural practices, including the reduction of synthetic fertilizers, has become a challenge for the agriculture sector. In this experimental work, the effect of the liquid fraction of digestate (by-product of the anaerobic digestion process) as a fertilizer was evaluated. The aim of the research was to verify to which extent digestate can affect growth and quality parameters of orange fruits, comparing the results to those obtained for fruits grown on soil treated with conventional mineral fertilizers. To assess the effectiveness of the treatments, different qualitative and quantitative parameters of Citrus fruits were measured. In particular, the results showed slight differences between the two treatments, suggesting that digestate may be used for the production of high-quality fruits. Moreover, in some orchards, the Citrus fruits of the plants treated with digestate showed a higher concentration of health-promoting compounds, such as vitamin C, flavonoids, phenolic content, when compared to the control group. Thus, digestate can be considered an optimal source of plant nutrients and can be used as a crop growth promoter, since it represents an effective strategy for reducing the mineral fertilizers input.